A novel high-entropy monoboride (Mo0.2Ta0.2Ni0.2Cr0.2W0.2)B with superhardness and low thermal conductivity. Issue 17 (1st December 2020) - Zhao, Pengbo; Zhu, Jinpeng; Zhang, Yilin; Shao, Gang; Wang, Hailong; Li, Mingliang; Liu, Wen; Fan, Bingbing; Xu, Hongliang; Lu, Hongxia; Zhou, Yanchun; Zhang, Rui
Abstract: A new high-entropy monoboride (Mo0.2 Ta0.2 Ni0.2 Cr0.2 W0.2 )B ceramic with a WB-type orthogonal structure was designed and synthesised by in-situ reactive hot pressing at 2000 °C and 30 MPa for 1.5 h under an argon atmosphere. The microstructure of the sintered samples was comprehensively characterised, and the formation of a high-entropy monoboride (Mo0.2 Ta0.2 Ni0.2 Cr0.2 W0.2 )B ceramic was confirmed. Owing to the high density of the dislocations and strengthening metal-boron bonds, the high-entropy (Mo0.2 Ta0.2 Ni0.2 Cr0.2 W0.2 )B ceramic exhibited a hardness of 48.51 ± 4.07 GPa, which enabled it to be classed as a new superhard material. In addition, the thermal conductivity (2.05 ± 0.10 W/(m·K) at 400 °C) and electric conductivity (132.30 S/cm) were determined.